Prevalence and Severity of Pain in Cancer Patients in Germany - Broemer, Laura; Hinz, Andreas; Koch, Uwe; Mehnert-Theuerkauf, Anja (Frontiers in Pain Research, 2021)
Pain is a common symptom in cancer patients, restricts daily life activities and reduces survival time. Identification of sociodemographic, medical and psychological correlates of pain among cancer patients in Germany could help identify subgroups most in need of pain management. In this multicenter, epidemiologic cross-sectional study, we assessed pain prevalence and severity, quality of life (QoL) and psychological distress in a sample of 3,745 cancer patients across all tumor entities. In total, 37.9% patients suffered from cancer-related pain and 56.1% suffered from non-specific pain. Younger, female, less educated and unemployed patients reported pain more frequently and more severe pain (p < 0.001). Pain was associated with distress, depression, anxiety, QoL, tumor stage (p < 0.001), and time since diagnosis (p = 0.012). Pain assessment and pain management should be a routine part of cancer treatment and cancer survivorship care plans.